Conductively driven, high-thermal gradient metamorphism in the Anmatjira Range, Arunta region, central Australia - Anderson, J.; Kelsey, D.; Hand, M.; Collins, William (Wiley - Blackwell, 2013)
LA-ICP-MS in situ U-Pb monazite geochronology and P-T pseudosections are combined to evaluate the timing and physical conditions of metamorphism in the SE Anmatjira Range in the Aileron Province, central Australia. All samples show age peaks at c. 1580-1555 Ma, with three of five samples showing additional discrete age peaks between c. 1700 and 1630 Ma. P-T phase diagrams calculated for garnet-sillimanite-cordierite-K-feldspar-ilmenite-melt bearing metapelitic rocks have overlapping peak mineral assemblage stability fields at ~870-920 °C and ~6.5-7.2 kbar. P-T modelling of a fine-grained spinel-cordierite-garnet-biotite reaction microstructure suggests retrograde P-T conditions evolved down pressure and temperature to ~3-5.5 kbar and ~610-850 °C. The combined geochronological and P-T results indicate the SE Anmatjira Range underwent high-temperature, low-pressure metamorphism at c. 1580-1555 Ma, and followed an apparently clockwise retrograde path. The high apparent thermal gradient necessary to produce the estimated P-T conditions does not appear to reflect decompression of high-P assemblages, nor is there syn-metamorphic magmatism or structural evidence for extension. Similar to previous workers, we suggest the high-thermal gradient P-T conditions could have been achieved by heating, largely driven by high heat production from older granites in the region.